MNEs and information management : structuring and governing IT resources in the global enterprise - Markus, M. Lynne (2013)
This paper for the 20 th anniversary issue of the Journal of Global Information Management (JGIM) looks back on the last ten years of research on two related areas highlighted in Tan and Gallupe's (1999) manifesto for research on global information management in the decade ahead: global enterprise management and global management of information resources. In particular, the paper examines the relationship between the structure and governance of multinational enterprises (MNEs) and the structure and governance of IT resources in MNEs. Early IS research hypothesized alignment between enterprise organization structure and the structure of the IT function in high-performing organizations. However, research on "structure" in both MNEs and IT resources shifted to the concept of "governance". This paper argues that IT organization design (structure and governance in combination) should be the focus of future research on IT resources management in MNEs. In addition, the paper argues that the relationship between MNE design and IT resources management is a critical topic. The paper examines three relationships among these two concepts: the contingency theory argument that IT resources management should follow and be aligned with MNE organization design, the universalistic argument that there is one best way to organize IT resources in MNEs, and the co-evolutionary argument that IT enterprise resources management design can lead, as well as follow, MNE organization design.